Back to work: growing with jobs in Europe and Central Asia - Arias, Omar S.; Sánchez-Páramo, Carolina; Dávalos, María E.; Santos, Indhira; Tiongson, Erwin R.; Gruen, Carola; de Andrade Falcão, Natasha; Saiovici, Gady; Cancho, Cesar A. (Washington, DC, 2014)
"Creating more and better jobs is arguably the most critical challenge to boosting shared prosperity in ECA. This report answers two questions: How can the countries create more jobs? Should there be specific policies to help workers access those jobs?. In answering them, the report examines the role of reforms, firms, skills, incentives and barriers to work, and labor mobility through the lens of two contextual factors: the legacy of centralized planned economies and the mounting demographic pressures associated with rapid aging in some countries and soaring numbers of youth entering the workforce in others. The main findings of the report are: i) market reforms pay off in terms of jobs and productivity, although with a lag; ii) a small fraction of superstar high-growth firms, largely young, account for most of new jobs created in the region- thus, countries, especially late reformers, need to unleash the potential of high levels of latent entrepreneurship to start-up new firms; iii) skills gaps hinder employment prospects, especially of youth and older workers, due to the inadequate response of the education and training system to changes in the demand for skills; iv) employment is hindered by high implicit taxes on work for those transitioning to work from inactivity or unemployment and barriers that affect especially women, minorities, youth and older workers; and, v) low internal labor mobility prevents labor relocation to places with greater job creation potential. The report argues that to get more people back to work by growing with jobs, countries need to regain the momentum for economic and institutional reforms that existed before the crisis in order to: (i) lay the fundamentals to create jobs for all workers, by pushing reforms to create the enabling environment for existing firms to grow, become more productive, or exit the market and tap on entrepreneurship potential for new firms to emerge and succeed or fail fast and cheap; and (ii) implement policies to support workers so they are prepared to take on the new jobs being created, by having the right skills, incentives and access to work, and being ready to move to places with the highest job creation potential."